Translating IT Terminology in Educational Textbooks (e-Journal of Linguistics, 2026)
Technological term is a crucial aspect in the advancement of science and technology. Translating these terms from English into Indonesian requires a deep understanding of their linguistic forms, particularly the noun classes that dominate the field. Nouns in technological terminology range from technical and abstract terms to culturally bound concepts, each of which presents unique translation challenges. This study examines the procedures used to translate nouns in English technological terms into Indonesian, focusing on accuracy and readability to the preferences of the target readers. By categorizing terms into singular nouns, proper nouns, and common nouns, and analyzing the translation procedures through the Single Approach (SA) and Pair Approach (PA), this study highlights the dominance of certain procedures. The research findings indicate that the PA with its combined procedures that integrate semantic and communicative translation is effective in maintaining terminological integrity while ensuring cultural and contextual relevance. This study emphasizes the urgency of having systematic translation guidelines to improve the consistency and quality of technical term in Indonesia.